The Main Strategy of MSMEs Able to Survive in the Upcoming Latest Variant of Covid-19 - syafril; Mohdari; Syaifullah; Andi Makkulawu Panyiwi Kessi; Muhammad Fahmi; Neti Rosiana Fadilah (MultiTech Publisher, 2023)
Research on the Main Strategy for MSMEs to Survive in the Face of the Latest Variants of Covid-19 in the Future is very useful research in dealing with similar problems if it happens again. This research is a qualitative research using the Netnography method with the Social Network Analysis approach through the MSME Business Actors Group on Facebook and WhatsApp. Data collection was carried out using a technical questionnaire using the Google Form application which was distributed on the MSME group's social media. The results of the study show that several strategies implemented by MSME business people have made them able to survive in the midst of a crisis storm during the Covid-19 pandemic. This research is very useful for business people and researchers in the future if there is a pandemic problem and other similar problems.